Contribution of mobile sources to secondary formation of carbonyl compounds. (1st December 2020) - Cook, Rich; Phillips, Sharon; Strum, Madeleine; Eyth, Alison; Thurman, James
ABSTRACT: In the 2014 National Air Toxics Assessment (NATA), the carbonyl compounds formaldehyde and acetaldehyde were identified as key cancer risk drivers and acrolein was identified as one of the three air toxics that drive most of the noncancer risk. In this assessment, averaged across the Continental United States, about 75% of ambient formaldehyde and acetaldehyde, and about 18% of acrolein, is formed secondarily. This study was conducted to estimate the potential contribution to these secondarily formed carbonyl compounds from mobile sources. To develop such estimates, we conducted several CMAQ runs, where emissions are set to zero for different mobile source sectors, to determine their potential contribution. Although zeroing out emissions from an individual sector can offer only a rough approximation of how the sector might contribute to overall secondary concentrations, our results suggest that across the U. S., mobile sources contribute about 6–18% to secondary formaldehyde, 0–10% to secondary acetaldehyde, and 0–70% to secondary acrolein, depending on location. Implications : Photochemical modeling of carbonyl compounds was conducted with emissions set to zero for various mobile source sectors to determine their contribution to secondary concentrations. Results indicated mobile sources contributed to total and secondary concentrations of formaldehyde, acetaldehyde, and acrolein in many locations across the U.S. with acrolein the dominant contributor in some locations. However, biogenic sources dominated secondary formaldehyde and acetaldehyde, and fires dominated secondary acrolein.